New High‐Pressure Forms of Al2SiO5. Issue 16 (20th August 2018) - Zhou, Y.; Irifune, T.; Ohfuji, H.; Kuribayashi, T.
Abstract: Phase relations of Al2 SiO5 have been studied by multianvil experiments at pressures of 13–23 GPa and temperatures of 2000–2900 K. Al2 SiO5 kyanite was found to transform into two new high‐pressure forms of Al2 SiO5 (kyanite II and III) at temperatures exceeding 2300–2500 K and pressures of 14–23 GPa: The first phase transition occurs near 14 GPa, and the second occurs near 17 GPa. The new Al2 SiO5 phases have triclinic and monoclinic crystal symmetries with zero‐pressure densities of 3.876(2) and 3.982(1) g/cm 3, respectively, which are significantly denser than kyanite ( ρ 0 = 3.666 g/cm 3 ) but less dense than the isochemical mixture of Al2 O3 corundum and SiO2 stishovite ( ρ 0 = 4.036 g/cm 3 ). The exceptionally high stability temperatures of the new Al2 SiO5 phases suggest that they are unlikely to form in the present mantle but may be found in some impact craters and shocked meteorites and act as important indicators of pressure and temperature for the shock events. Plain Language Summary: Aluminosilicate in the mantle is an important issue for Earth science. Previous studies argued the existence of a high‐pressure form of Al2 SiO5 in the lower mantle, in addition to those of the well‐known polymorphs, andalusite, sillimanite, and kyanite, found in shallow metamorphic rocks. However, the existence of such a high‐pressure form of Al2 SiO5 has been controversial among previous studies, due to the large discrepancies in its stability region and crystal structure. Here we figure out the phase relations of Al2 SiO5 at mantle‐transition‐region pressures ( 13–23 GPa, corresponding to 410–660 km in depth) and temperatures of 2000–2900 K via multianvil high‐pressure experiments and show that kyanite transforms into two new high‐pressure forms of Al2 SiO5 at temperatures exceeding 2300–2500 K in the pressure range of 14–23 GPa: The first phase transition occurs near 14 GPa, and the second occurs near 17 GPa. Although the extremely high stability temperatures of the new Al2 SiO5 phases suggest their absence in the present mantle, they may be found in some impact craters and shocked meteorites and act as important indicators of pressure and temperature for the shock events. Key Points: We investigated the phase relations of Al2 SiO5 by multianvil experiments at pressures of 13‐23 GPa and temperatures of 2000‐2900 K We confirmed the existence of two new high-pressure forms of Al2 SiO5 at pressures of 14‐23 GPa and temperatures exceeding 2300‐2500 K Meteoritic impact may cause potential natural formation of the new Al2 SiO5 phases